Starter culture technology: fermented foods - D. Prema Latha; S. M. Reddy; K. S. Youn; Ravindra Pogaku (Springer International Publishing, 2015)
Practice of starter culture is an age old practice but without any scientific basis. With the awareness of need of microbial inoculations for regulation of fermentation process for quality production of desired quality foods innovative development have taken place. Development of new strains for elite strain which can improve the quality, stability, flavor, texture and phage resistant starter cultures are raised on a variety of medium depending organism as well as product to be developed. The starter culture are classified based on their composition growth requirement and methods of propagation. These starter cultures are preserved by different methods they can be available all the time. Though commercial strains are available their isolation and subsequent improvement through different genetical methods are desirable to get a novel strains with unique properties of commercial importance. Among different microorganisms such as lactic acid bacteria, yeast (Saccharomyce cerevisae, Penicillium camembertii, P. roquefortii) and Rhyzopus (R. oryzae, R. sojae) are extensively used for this purpose. Perfection in the preparation, storage and propagation need to be improved. Mixed starters with symbiotic activity have to be formulated.